Reflections of the June 1940 Events in the Šiauliai Region in the Press of that Time - Juodis, Darius (Acta humanitarica academiae Saulensis, 2026)
The article examines Lithuanian press coverage from the second half of June 1940 relating to events in Šiauliai. The research employs both analytical and descriptive methods. The study draws on the local newspaper Įdomus mūsų momentas (“Our Interesting Moment”), published in Šiauliai at the time, as well as the national Lithuanian press. The paper aims to identify the main themes in the press coverage and illustrate them with concrete examples.In the first half of June 1940, Lithuanian newspapers and journals did not publish any particularly notable reports clearly indicating rapid and fundamental changes in the country’s life, but the situation changed in the second half of the month, when Soviet authority began to establish themselves in Lithuania.The press of that time often wrote about the presence of the Red Army in Šiauliai as an undeniable and significant factor, although this was later downplayed in Soviet-era literature. It also reported on changes among leading officials in the Šiauliai region, without providing detailed explanations of these issues. The press also mentioned the first cases of people fleeing from Šiauliai abroad.Most attention in the press was devoted to the pro-Soviet rally held in Šiauliai on June 27, without revealing the behind-the-scenes aspects of its organisation. It is noteworthy that the reproduction of speeches from the rally and their quotations in the press reflected further steps by the Soviet authorities. Another event of national importance that took place in Šiauliai was the release of political prisoners (communists) from prison, which received considerable coverage in the press.In addition to political developments, the press also included information of a more domestic (economic) nature, although these were overshadowed by political events. These non-political events may have been described more objectively by the press.It can be assumed that all press publications, being subject to censorship, did not necessarily reflect the real situation or the actual course of events in Šiauliai and across Lithuania.
Keywords: June 1940; Šiauliai; press; Soviet government; Red Army; rallies